Correlation of Serum CysC, IMA, and LP-PLA2 Levels With Type 2 Diabetes Mellitus Patients With Lower Extremity Atherosclerotic Occlusive Disease - Feng, Fen; Chen, Yong; Wang, Gang; Huang, Ping; Zhu, Qiaolin; Zhou, Bin (Frontiers in Surgery, 2022)
Objective: To investigate the serum CysC,ischemia modified albumin (IMA) and LP-PLA2 in patients with type 2 diabetes mellitus (T2DM) combined with lower extremity atherosclerotic occlusive disease (LEASOD) and their correlation. Methods: A total of 110 patients with T2DM combined with LEASOD admitted to our hospital from March 2017 to December 2019 were selected as the observation group. A total of 110 healthy people who had a physical examination in our hospital during the same period were selected as the control group. Serum CysC, IMA, LP-PLA2 and ankle-brachial index (ABI) were detected in each group. The observation group was divided into mild group, moderate group and severe group according to the ABI index. Analyze the diagnostic value of the relationship between serum CysC, IMA, LP-PLA2 levels and the condition of the disease.Results: The serum levels of CysC, IMA and LP-PLA2 in the observation group were higher than those in the control group. The serum levels of CysC, IMA and LP-PLA2 in the severe group and moderate group were higher than those in the mild group, and the serum levels of CysC, IMA and LP-PLA2 in the severe group were higher than those in the moderate group. Pearson correlation analysis showed that CysC, IMA, LP-PLA2 levels were both negatively correlated with ABI. ROC curve results showed that the AUC of serum CysC in the diagnosis of T2DM combined with LEASOD was 0.806, and the best cut-off value was 1.74 mg/L. The AUC of serum IMA for diagnosis of T2DM combined with LEASOD was 0.772, and the best cut-off value was 92.58g/L. The AUC of serum LP-PLA2 in the diagnosis of T2DM combined with LEASOD was 0.781, and the best cut-off value was 544.86ng/L. The AUC of the three combined diagnosis of T2DM combined with LEASOD was 0.863. Conclusion: The higher the serum CysC, IMA, LP-PLA2 levels, the more severe the occlusion of lower extremity arteriosclerosis, which can be used as important serum markers to monitor the severity of T2DM with LEASOD. Combined detection of serum CysC, IMA and LP-PLA2 has a good diagnostic value for patients with T2DM combined with LEASOD.